Protokol za klinično kirurško tutorstvo: Gradivo za študente medicine in študente tutorje (University of Maribor Press, 2025)
Protocol for Clinical Surgical Tutoring: Study Material for Medical Students and Student Tutors. Protocol for Clinical Surgical Tutoring, from the idea to the publication, is a product of University of Maribor Faculty of Medicine graduates, young doctors, who started the work during their study years. The study material shines a light on a variety of topics, from informed consent to surgical suturing alternatives, including the basics of the code .of conduct in the operating theatre, presentation of surgical instruments, setting an antiseptic sterile field and sutures with tying. Protocols are written step-by-step and the text is accompanied by illustrations, made by a fellow graduate, a young doctor herself aswell. This study material is the result of hard work and collaboration of colleagues and mentors; all who contributed wish that it will serve its purpose.